Carbon foil, charge conversion foil

JP2026169295APending Publication Date: 2026-10-16JAPAN ATOMIC ENERGY AGENCY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026179864
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0013】 本発明は以上のように構成されているので、炭素のみを主成分とした寿命の長い荷電変換フォイルを得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169295000001_ABST
    Figure 2026169295000001_ABST
Patent Text Reader

Abstract

To obtain a long-life charge conversion foil with carbon as the main component. [Solution] Figures 9(a) and 9(b) are optical microscope images of carbon foil after peeling from a substrate with an anode diameter of 20 mm (Rc=0.579) (Example), at two different magnifications (a: low magnification, b: high magnification). Here, the surface of the carbon foil after peeling following swelling and heat treatment, as described above, is shown. In both, numerous regions separated by linear boundaries are recognized, but the size of these regions differs significantly between the comparative example and the example (Figure 9). In the carbon foil of the comparative example, the surface density of such regions is 100 mm². 2 While there are approximately 28 per unit, in the carbon foil shown in Figure 9, there are 1 mm 2 There were about 90 of them.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention uses carbon as its main component did This invention relates to carbon foil and charge conversion foil using this carbon foil. [Background technology]

[0002] In accelerators that accelerate positive heavy ions or protons (positively charged particles), charge conversion foils are used to strip electrons from negative ions of the corresponding element (negative hydrogen ions in the case of protons) to convert them into positive ions, or to further strip electrons from positive ions to increase their charge. By passing the beam of negative ions through this charge conversion foil, the negative ions are converted into positive ions. Carbon foil, mainly composed of carbon, is particularly preferred as this charge conversion foil, and its required thickness depends on the ion species and energy of the ion beam incident on the carbon foil. For example, for hydrogen negative ions with a voltage of several hundred MeV, the required thickness is about a few μm (several hundred μg / cm³ in terms of surface density). 2 It is of a certain degree.

[0003] Therefore, during use, the charge conversion foil undergoes degradation (shrinkage and deformation) due to ionic shocks caused by the irradiated negative or positive ion beam. This degradation can lead to mechanical failure of the charge conversion foil (such as fracture), and thus, extending its lifespan due to this degradation is required. Furthermore, as mentioned above, the charge conversion foil is used in the form of a thin film. In its manufacture, it is generally formed as a thin film on a substrate using methods such as vapor deposition, and then this thin film is peeled off the substrate to form an independent foil in thin film form. In this case, it is required that a thin film of the desired thickness be stably formed on the substrate without peeling, and that this thin film can be reliably peeled off afterward. In other words, it is required that such a manufacturing method can be realized with high reproducibility.

[0004] Considering the above points, Non-Patent Document 1 describes a method for manufacturing carbon foil (charge conversion foil) by generating an arc discharge with a carbon electrode in a vacuum, depositing a carbon thin film onto a substrate, and then peeling it off. However, in order to extend the lifespan before the aforementioned failure occurs, the carbon foil is required to have a certain thickness. In this manufacturing method, however, the carbon thin film tends to peel off the substrate before it reaches such a thickness during deposition, as described in Patent Document 1, thus limiting its thickness. Therefore, from this perspective, it has been difficult to obtain a charge conversion foil with a long lifespan.

[0005] Patent Document 1 describes how, by mixing boron (B) into the carbon in a carbon electrode, a boron-added carbon foil (HBC foil) can be manufactured in the same way, and because delamination during film formation does not occur, it can be made thicker (10 μg / cm²). 2 It is stated that the above can be achieved. Furthermore, it is stated that the boron added in this way does not adversely affect the durability against ion irradiation, thereby extending the lifespan of this HBC foil compared to carbon foil without boron. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] "Development of Charge Conversion Carbon Thin Films for Heavy Ion Accelerators: A Challenge for Long Lifespan and High Strength," Isao Sugai, Journal of the Physical Society of Japan, Vol. 43, No. 1, p44 (1988) [Patent Documents]

[0007] [Patent Document 1] International Publication No. 2007 / 058224 [Overview of the project] [Problems that the invention aims to solve]

[0008] The technology described in Patent Document 1 allows for the production of thick charge conversion foils, thus extending the lifespan before fracture occurs. However, as presented in "Challenges to Charge Conversion Using Pure Carbon Foils in the J-PARC 3GeV Synchrotron," by Takamitsu Nakanoya, Masahiro Yoshimoto, Pranab Saha, Osamu Takeda, Rioji Saeki, and Masayoshi Muto at the 20th Annual Meeting of the Japan Society for Accelerator Research (2023), FRP38, when the irradiation intensity of the negative ion beam irradiating the charge conversion foil was increased to increase the accelerator beam current, warping (deformation) sometimes occurred, although fracture (cracks, etc.) did not occur. On the other hand, such warping (deformation) was less common with pure carbon foils. Therefore, such deformation may be due to the addition of boron to the carbon.

[0009] Furthermore, since the manufacturing cost of boron-doped carbon electrodes is significantly higher than that of pure carbon electrodes, and considering that the electrodes used in this case are consumables, it was desirable to obtain a long-life charge conversion foil using an electrode whose main component is carbon and which contains only unavoidable impurities.

[0010] Therefore, a long-life charge conversion foil was desired, which would consist primarily of carbon without the addition of boron.

[0011] This invention has been made in view of the above-mentioned problems, and aims to provide an invention that solves the above-mentioned problems. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention has the following configuration. Book The carbon foil of the invention is characterized in that, in a plan view, it is formed by a mixture of particles with a particle size in the range of 100 nm to 500 nm and particles with a particle size in the range of 1 nm to 5 nm, linear protrusions are formed in a mesh-like pattern on the surface, and multiple substantially flat regions with an average diameter in the range of 50 μm to 250 μm are formed, separated by these protrusions, and is composed only of carbon and unavoidable impurities. The charge conversion foil of the present invention is characterized by being composed of the carbon foil. The charge conversion foil of the present invention is composed of the aforementioned carbon foil, and has a thickness of 5 μg / cm 2 or more, characterized in that.

Effects of the Invention

[0013] Since the present invention is configured as described above, a long-life charge conversion foil containing only carbon as the main component can be obtained.

Brief Description of the Drawings

[0014] [Figure 1] This is a diagram showing the configuration of a manufacturing apparatus used in the method for producing a carbon thin film (carbon foil) according to an embodiment of the present invention. [Figure 2] This is the result of measuring the anode electrode diameter dependency of the cathode ratio in the carbon foil produced by the manufacturing method according to the embodiment of the present invention. [Figure 3] This is the relationship between the service life and the anode electrode diameter when the carbon foil produced by the manufacturing method according to the embodiment of the present invention is used as a charge conversion foil. [Figure 4] This is the relationship between the service life and the cathode ratio when the carbon foil produced by the manufacturing method according to the embodiment of the present invention is used as a charge conversion foil. [Figure 5] This is a table showing the correspondence relationship among the anode diameter, the anode / cathode area ratio, the cathode ratio, and the service life in the manufacturing method and carbon foil according to the embodiment of the present invention. [Figure 6] This is an SEM photograph of the surface of the carbon foil according to the embodiment of the present invention. [Figure 7] This is a diagram schematically showing the microscopic planar structure of the carbon foil according to the embodiment of the present invention. [Figure 8] This is an optical microscope photograph of the surface of a carbon foil serving as a comparative example. [Figure 9] This is an optical microscope photograph of the surface of a carbon foil serving as an example. [Figure 10] This is a diagram schematically showing the macroscopic cross-sectional structure of the carbon foils of the comparative example and the example. [Figure 11] This is a photograph of the surface morphology of a carbon foil used as a comparative example, showing the process leading up to fracture after irradiation with an ion beam. [Figure 12] This is a photograph of the surface morphology of a carbon foil used as an example, showing the process leading up to fracture after irradiation with an ion beam. [Modes for carrying out the invention]

[0015] The following describes a method for manufacturing carbon foil according to an embodiment of the present invention. Figure 1 is a schematic diagram showing the configuration of a carbon thin film manufacturing apparatus 1 used in this manufacturing method. In this manufacturing apparatus 1, similar to Non-Patent Document 1, a carbon thin film is formed on a substrate 100 by an arc discharge method using a carbon electrode, and this is peeled off from the substrate 100 to become an independent carbon foil (charge conversion foil) in a thin film state.

[0016] In this manufacturing apparatus 1, a substrate holder 11 is provided in a vacuum chamber 10 whose interior is evacuated to a vacuum, holding the substrate 100 facing downwards in the figure. Below the substrate holder 11, a positive carbon electrode 21 and a negative carbon electrode 22 are fixed to electrode holders 23 and 24, respectively, so that they face each other horizontally. A positive potential and a negative potential are applied to the positive carbon electrode 21 and the negative carbon electrode 22 from an external DC power supply 30 via the electrode holders 23 and 24, respectively. This allows an arc discharge to occur between the positive carbon electrode 21 and the negative carbon electrode 22, causing carbon atoms to evaporate from the opposing surfaces of the positive carbon electrode 21 and the negative carbon electrode 22 (positive carbon electrode surface 21A and negative carbon electrode surface 22A), with some of these reaching the surface of the substrate 100 to form a thin film. The thickness of the thin film is determined by the magnitude of the arc current and the duration for which the arc discharge occurs. Furthermore, the substrate holder 11 (substrate 100) may be configured to rotate in order to make the thickness of the carbon thin film on the substrate 100 uniform in plane.

[0017] In the example described later, a glass substrate was used as the substrate 100, which is preferable when peeling off the carbon thin film. However, the material and form of the substrate 100 can be appropriately determined depending on the purpose of using the carbon thin film and whether or not the carbon thin film is peeled off from the substrate 100. For example, if the carbon thin film is used as a heat dissipation component, the substrate 100 may be a semiconductor or a heat sink. In addition, if it is desired to form the carbon thin film only in a specific area, the substrate 100 may be surrounded by a component having an opening.

[0018] The vacuum chamber 10 is evacuated by a vacuum pump (not shown) at the lower right side of the figure, and the vacuum level is approximately as described in Patent Document 1 (5 × 10 during arc discharge). -4 The current is maintained at approximately Pa. In addition, a thickness gauge 40 is provided near the substrate 100, on which a carbon thin film is formed in the same manner as the substrate 100. By monitoring the electrical or mechanical properties, the thickness of the carbon thin film formed on the substrate 100 is indirectly recognized during film formation. Therefore, when it is recognized that a carbon thin film of the desired thickness has been formed on the substrate 100, the arc discharge can be stopped, and a carbon thin film of the desired thickness can be obtained. The arc discharge current is set to approximately 500A.

[0019] The above configuration is the same as the technology described in Non-Patent Document 1 and Patent Document 1. The positive carbon electrode 21 and negative carbon electrode 22 used in this manufacturing apparatus 1 are both formed of isotropic graphite. Anisotropic graphite or the like may also be used. This material is mainly composed of carbon and, excluding unavoidable impurities, does not contain other elements like those in the technology described in Patent Document 1. Therefore, the carbon thin film formed on the substrate 100 by this method is also mainly composed of carbon. In this respect, it differs from the technology described in Patent Document 1 and is the same as the technology described in Non-Patent Document 1. Furthermore, both the positive carbon electrode 21 and the negative carbon electrode 22 are cylindrical in shape with the left-right direction in the figure as the central axis, and the positive carbon electrode surface 21A and the negative carbon electrode surface 22A, which face each other in the figure, are both circular in shape.

[0020] In this case, carbon particles are released from the positive carbon electrode 21 and the negative carbon electrode 22 due to localized heating by arc discharge and irradiation of the electrode surface with electrons and ions associated with the arc current, respectively, and a carbon thin film is formed by the deposition of these carbon particles on the substrate 100. Non-patent document 1 states that in this case, if the amount of carbon particles released from the negative carbon electrode and the positive carbon electrode, respectively, are Wc and Wa, the ratio of Wc in the formed carbon thin film (cathode ratio Rc = Wc / (Wa + Wc)) greatly affects the lifetime of this carbon thin film when it is used as a charge conversion foil. Here, Wc and Wa are calculated from the amount of wear on the negative carbon electrode and the positive carbon electrode after film formation, respectively.

[0021] Non-patent document 1 states that in this case, the lifetime is longer when the cathode ratio Rc is large, especially between 60% and 70%. During arc discharge, the positive carbon electrode is irradiated mainly with electrons or negative ions generated from residual gas, while the negative carbon electrode is irradiated mainly with positive ions. Furthermore, the beam shape of the current during arc discharge differs between the positive and negative carbon electrodes. Therefore, even if these electrodes are made of the same material (graphite), the emission of carbon particles and the morphology of the carbon particles released will differ between the positive and negative sides. The dependence of the lifetime on the cathode ratio Rc is thought to be because it reflects the difference in the morphology of the carbon particles emitted from the positive and negative carbon electrodes, and the ratio of these two types of carbon particles affects the lifetime.

[0022] This cathode ratio Rc changes depending on the film deposition conditions. For this reason, in Non-Patent Literature 1, carbon thin films with various cathode ratios Rc were manufactured by using cylindrical shapes with a diameter of 10 mm for both the positive and negative carbon electrodes and changing the film deposition conditions, and the dependence of the lifetime on the cathode ratio Rc was measured.

[0023] In this regard, Non-Patent Document 1 states that when the cathode ratio Rc is close to 0%, the mechanical strength of the carbon thin film is very high, but the aforementioned lifespan is short. When the cathode ratio Rc is close to 100%, the lifespan is long when compared with the same film thickness, but the mechanical strength is low. Patent Document 1 also states that such carbon thin films without boron doping are prone to delamination during film formation. In order to obtain a long lifespan, a charge conversion foil of a certain thickness or more is necessary, but with conventional methods, it is not possible to obtain a thick carbon foil due to delamination during film formation, and as a result, a long lifespan cannot be obtained.

[0024] The inventors have found that by making the shapes of the positive carbon electrode 21 and the negative carbon electrode 22 asymmetrical, they can solve the above-mentioned problems described in Patent Document 1 and deposit a carbon thin film that has a high cathode ratio and a long lifespan as a charge conversion foil. This point will be explained below.

[0025] As described above, both the positive carbon electrode 21 and the negative carbon electrode 22 are cylindrical in shape with a common central axis (left-right direction in the figure) in the arrangement shown in Figure 1. In this case, carbon particles are mainly emitted from the circular positive carbon electrode surface 21A of the positive carbon electrode 21 that faces the negative carbon electrode 22, and from the circular negative carbon electrode surface 22A of the negative carbon electrode 22 that faces the positive carbon electrode 21. Here, the positive carbon electrode 21 is set to be thicker than the negative carbon electrode 22. In this case, the current density associated with arc discharge does not change on the negative carbon electrode 22 side because the electrode thickness is constant, but on the other hand, if the positive carbon electrode 21 side is made thicker, this current density can be lowered and the heat dissipation efficiency is increased, so the temperature rise can be lower than before the thickness was increased. For this reason, this configuration makes it possible to make the situation when carbon particles are emitted on the positive carbon electrode 21 side more significantly different from that on the negative carbon electrode 22 side, and makes it possible to adjust the cathode ratio Rc over a wider range.

[0026] Figure 2 shows the measurement results of the cathode ratio Rc when a glass substrate is used as the substrate 100, with the diameter of the negative carbon electrode 22 (cathode: negative carbon electrode surface 22A) fixed at 10 mm and the diameter of the positive carbon electrode 21 (anode: positive carbon electrode surface 21A) set to 10 mm, 15 mm, 18 mm, 20 mm, 25 mm, 30 mm, and 45 mm. Here, the current value was set to 500 A, and the cathode ratio Rc (Wc, Wa mentioned above) was calculated from the amount of wear on each electrode. From these results, it can be seen that by increasing the diameter of the positive carbon electrode 21 (anode), the amount of carbon particles released from the negative carbon electrode 22 side can be increased, and the cathode ratio Rc can be increased. Note that when the anode diameter is 45 mm, Rc exceeds 1 because carbon particles released from the cathode side reattach to the anode side. Therefore, an error of up to 0.15 occurs in Rc due to this reattachment. However, by employing such an asymmetrical electrode configuration, a wide range of cathode ratios Rc can be obtained.

[0027] Furthermore, in order to obtain the carbon thin film on its own from the glass substrate on which the above-mentioned carbon thin film is formed, moisture is added to the carbon thin film on the substrate to cause it to swell, and then the glass substrate in this state is immersed in water. This separates the carbon thin film from the glass substrate, resulting in a carbon foil form that can be used as a charge conversion foil. At this time, a wrinkle structure, as described later, is formed in the carbon thin film by swelling. The subsequent heat treatment temperature in a vacuum should be 200°C or higher, and the upper limit should be below the temperature at which the substrate does not deform. There are no particular restrictions on the heat treatment time, but for example, by performing heat treatment for 7 hours or more, this wrinkle structure can be fixed and maintained even after separation from the substrate. Without this heat treatment, the wrinkles will disappear when the glass substrate is immersed in water. In addition, the swelling treatment may be carried out using moisture in the atmosphere without the addition of moisture.

[0028] Here, we investigated the dependence of the lifetime on the anode diameter (cathode ratio Rc) when the thickness of the carbon thin film (carbon foil) was kept constant at 20 μg / cm² (actual film thickness is approximately 0.12 μm). Here, the lifetime was measured as the time until the carbon foil was destroyed when irradiated with 300 keV Ar ions at a beam current intensity of 1 μA. Figures 3 and 4 show the dependence of the lifetime on the anode diameter (Figure 3) and cathode ratio Rc (Figure 4) in this case. Figure 5 is a table showing the results from Figures 3 and 4.

[0029] These results show a significant difference in lifespan between anode diameters of 18 mm or more (anode / cathode area ratio Rs of 3.24, cathode ratio Rc of 0.483) and those with anode diameters less than 18 mm, with the former achieving a lifespan more than 20 times longer than the latter. This is presumed to be due to the electrode configuration described above, which resulted in a carbon particle structure within the carbon foil and high-density, fine wrinkles on the foil surface, as described later, that are particularly suitable for extending lifespan.

[0030] In other words, when using the above-described manufacturing apparatus 1, the cathode ratio Rc can be broadly controlled by changing the diameter of the positive carbon electrode 21 or the negative carbon electrode 22, and the lifespan can be significantly increased as shown in Non-Patent Literature 1. Furthermore, while Non-Patent Literature 1 shows a tendency for lifespan to decrease when the cathode ratio exceeds 70%, a characteristic feature of this method is that there is no tendency for lifespan to decrease when manufactured using this method.

[0031] In the above example, the carbon foil was obtained by peeling off a carbon thin film formed on a glass substrate by the above manufacturing method. However, the method for obtaining carbon foil from a carbon thin film formed on a glass substrate can be appropriately set depending on the form of the carbon foil. For example, as in the polycrystalline diamond foil described in Patent Document 1 (Comparative Example 1), the carbon thin film (carbon foil) can be partially separated from the substrate by partially removing the substrate on which the carbon thin film is formed from the back side, while using the carbon thin film in a form indicated by the substrate around this portion. In this case as well, swelling and heat treatment as described above can be performed in the same way.

[0032] Furthermore, when actually used as a charge conversion foil, for example, for a 400 MeV hydrogen negative ion, the foil should be 14 mm wide, 100 mm long, and 340 μg / cm thick. 2 The foil is formed to have a thickness of approximately 2 μm, and this thickness is actually achieved by folding a foil with a thickness of 170 μg / cm². Under any of the conditions shown in Figure 5, a carbon thin film of this thickness could be formed on the substrate 100, and after film formation, it could be peeled off to obtain a charge conversion foil. In other words, according to the above manufacturing method, a thicker carbon foil can be obtained compared to Non-Patent Document 1. In conjunction with the results shown in Figures 3 to 5, when the cathode / anode area ratio Rs is 3.24 or higher using the above manufacturing method, a particularly long-life carbon foil can be obtained.

[0033] Here, in Figure 5, the charge conversion foil of the above configuration was used in a 3 GeV proton synchrotron with an anode diameter of 20 mm. In this case, 400 MeV negative hydrogen ions were irradiated onto the charge conversion foil and converted to positive hydrogen ions (protons) with an efficiency of 99.7%, and these protons were then accelerated to 3 GeV. In this case, if the carbon foil described above was used as the charge conversion foil, the output would be 1.66 × 10⁻¹⁶. 21Even after irradiation with negative hydrogen ions, no fracture or warping (deformation) occurred. Therefore, this carbon foil can be used as a long-life charge conversion foil, and unlike the HBC foil described in "Challenge to Charge Conversion with Pure Carbon Foil in J-PARC 3GeV Synchrotron," Takamitsu Nakanoya, Masahiro Yoshimoto, Pranab Saha, Osamu Takeda, Rioji Saeki, and Masayoshi Muto, 20th Annual Meeting of the Japan Society for Accelerator Science (2023), no warping occurred.

[0034] As described in Non-Patent Document 1, this carbon thin film can be considered to be composed of carbon particles with small particle sizes (e.g., about 1-5 nm) and carbon particles with large particle sizes (e.g., about 100-500 nm), and it can be estimated that the former are emitted from the positive carbon electrode 21 and the latter from the negative carbon electrode 22. Therefore, in the various carbon thin films shown in Figure 5, the cathode ratio Rc reflects the relative abundance of these particles.

[0035] Figure 6 shows a film with a thickness of 200 μg / cm² deposited with an anode diameter of 20 mm and a cathode diameter of 10 mm. 2 This is a scanning electron microscope (SEM) image of a carbon thin film. Particulate structures with diameters of approximately 100 nm to 500 nm can be observed. Figure 7 is a schematic diagram illustrating this situation (microscopic planar structure). In the carbon thin film 200, large-diameter particles 210 with particle sizes in the range of 100 to 500 nm are dispersed and recognized, and the regions between the large-diameter particles 210 can be recognized as small-diameter particle regions 220 composed of small-diameter particles with particle sizes in the range of 1 to 5 nm. Here, "particle size" refers to the "equivalent diameter of a circle" as described in JIS Z 8827-1:2018, "Particle size analysis - Image analysis method - Part 1: Static image analysis method". The large-diameter particles 210 in Figure 6 can be recognized, for example, by the method described in this JIS document using an electron microscope image.

[0036] Note that since this carbon thin film 200 is porous, voids also exist in the small-diameter particle region 220, though the depiction thereof is omitted, and the area (volume) of the small-diameter particle region 220 described later is defined as excluding the voids. This situation is also described in Non-Patent Document 1, where large-diameter particles 210 are emitted from the cathode side, and small-diameter particles are emitted from the anode side. For this reason, a large cathode ratio Rc corresponds to a large abundance ratio of the large-diameter particles 210. Absorption of moisture by these voids contributes to swelling of the carbon thin film described later.

[0037] In this case, when the total area (actually the volume in the carbon thin film) occupied by the large-diameter particles 210 in FIG. 7 is defined as V2, and the total area of the small-diameter particle region 220 is defined as V1, V2 / V1 is equal to the aforementioned Wc / Wa, and in the most simplified model, Wc / Wa increases when the anode / cathode area ratio Rs is large (or increases when the cathode area is small). Therefore, when the value of V2 / V1 is 0.934 or more, which is the value of Wc / Wa when the area ratio Rs in FIG. 5 is 3.24 (the cathode ratio Rc is 0.483), the service life of this carbon foil can be extended.

[0038] At this time, if the charge conversion foil is thin, it is easily broken by ion bombardment, and sufficient charge conversion efficiency cannot be obtained, so the charge conversion foil is required to have a thickness equal to or greater than a certain value. The minimum value of such a thickness is, for example, 5 μg / cm which is the thickness of the sample shown in FIG. 3 2 or so. However, according to the aforementioned manufacturing method, a thicker charge conversion foil of 100 μg / cm 2 or more can be manufactured. Depending on the energy of the irradiated negative ion beam and the like, a charge conversion foil with a thickness greater than this may be used, but according to the above manufacturing method, this charge conversion foil can be manufactured even in that case. Alternatively, it is also possible to obtain a substantially even thicker charge conversion foil by folding and stacking the foil. By the above manufacturing method, a carbon foil having such a cathode ratio Rc and thickness can be easily obtained.

[0039] Next, we will describe the structure of this carbon foil on a larger scale than that shown in Figures 6 and 7. Figures 8(a) and 8(b) are optical microscope images of the carbon foil after exfoliation from the substrate, at two different magnifications (a: low magnification, b: high magnification), for the case where the anode diameter is 10 mm (Rc=0.043) (comparative example), and Figures 9(a) and 9(b) are optical microscope images of the carbon foil after exfoliation for the case where the anode diameter is 20 mm (Rc=0.579) (example). Here, the surface shape is shown on a larger scale than that shown in Figure 6. Here, the surface of the carbon foil after exfoliation following swelling and heat treatment, as described above, is shown. In both cases, numerous regions separated by linear boundaries are recognized, but the size of these regions differs significantly between the comparative example (Figure 8) and the example (Figure 9). In the carbon foil of Figure 8, the surface density of such regions is 100 mm 2 While there are approximately 28 per unit, in the carbon foil shown in Figure 9, there are 1 mm 2 There were about 90 of them.

[0040] Figure 10 schematically shows the cross-sectional structure of these shapes. As described above, this carbon foil (carbon thin film 200) is peeled from the substrate 100, and wrinkles are formed on the surface due to swelling treatment during this process. The linear boundaries in Figures 8 and 9 are the protrusions 250 that form wrinkles on the surface opposite to the substrate 100 at this time. Also, as shown in the figures, the region between the protrusions 250 becomes a substantially flat region parallel to the surface of the substrate 100, and these are the regions recognized in Figures 8 and 9. The width of the protrusions 250 is about 30 μm, as can be clearly seen in the optical microscope images shown in Figures 8 and 9. In other words, the above manufacturing method yields a carbon foil having many regions on its surface partitioned by such a mesh-like structure of protrusions. The size of this region depends on the cathode ratio Rc, etc., similar to the particle size mentioned above. The size of this region differs significantly between Figure 8 and Figure 9.

[0041] Figure 11 shows the surface morphology of a carbon foil with an anode diameter of 10 mm (Rc=0.043) (comparative example: carbon foil in Figure 8) after ion beam irradiation, captured until fracture. In this case, the area near the irradiation point gradually became mirror-like due to irradiation, and eventually fractured. Mirrorization occurs because the carbon foil in the irradiated area shrinks due to irradiation, causing the convex areas to disappear. It is thought that the carbon foil becomes unable to withstand this shrinkage, leading to fracture.

[0042] On the other hand, Figure 12 shows the surface morphology until fracture when the same ion beam was irradiated onto a carbon foil with an anode diameter of 20 mm (Rc = 0.579) (Example: Carbon foil in Figure 9). In this case as well, shrinkage due to mirroring progresses gradually and leads to fracture, but the change is slower compared to Figure 11, resulting in a longer lifespan. This is presumed to be because the high density of the protrusions 250 increases the effective surface area of ​​the carbon foil, thereby mitigating the progression of shrinkage due to irradiation. Furthermore, the high density of the protrusions 250 also contributes to higher heat dissipation efficiency due to the increased surface area. In other words, the larger surface area of ​​the carbon foil in Figure 9 compared to the carbon foil in Figure 8 contributes to its longer lifespan.

[0043] In other words, in this carbon foil, the wrinkle structure shown in Figure 10, and the high density of these wrinkles (protrusions 250), contribute to its long lifespan. The density of these protrusions 250 can be determined by the average diameter of the region partitioned by these protrusions (similar to the particle size mentioned above) in Figure 9. In carbon foil manufactured by the above manufacturing method, when the anode / cathode area ratio Rs is 3.24 or higher, this average diameter is in the range of 50 μm to 250 μm. That is, by setting the particle size of the particles constituting the carbon foil as described above, and setting the average diameter of the region partitioned by the wrinkles (protrusions 250) in this way, a charge conversion foil with a particularly long lifespan can be obtained.

[0044] The wrinkle structure described above is mainly formed by the swelling and heat treatment of the carbon thin film before delamination, as described above. In this case, the combination of setting the particle size of the particles constituting the carbon thin film as described above and this structure makes it possible to give this carbon foil (charge conversion foil) a particularly long lifespan. In particular, when a carbon thin film with a high cathode ratio Rc is formed using the manufacturing apparatus 1 in Figure 1, delamination does not occur until the stage of such swelling and heat treatment, so a carbon foil like the one in the above example can be obtained. Furthermore, when the cathode ratio Rc is large, the proportion of particles with a large particle size increases, so the diameter of the voids formed inside also increases, and the amount of water absorbed increases. As a result, the effect of swelling becomes greater, and dense, fine wrinkles are formed.

[0045] The carbon foil described above was used as a charge conversion foil to convert negative ions into positive ions (or protons). However, by passing positive ions through this carbon foil, electrons can be stripped from the positive ions, further increasing their valence. Furthermore, carbon foils with high ion irradiation resistance and mechanical strength in thin film states, as described above, can be used for other applications (e.g., heat dissipation components). In other words, the carbon foil described above is effective in applications other than charge conversion foils. [Explanation of symbols]

[0046] 1. Carbon thin film manufacturing apparatus 10 Vacuum Chamber 11. PCB holder 21 Positive carbon electrode 21A Positive side carbon electrode surface 22 Negative carbon electrode 22A Negative carbon electrode surface 23, 24 Electrode holder 30 DC power supply 40 Film Thickness Gauge 100 circuit boards 200 carbon thin film 210 Large-diameter particles 220 Small particle area 250 protrusions

Claims

1. In a plan view, The material is formed by a mixture of particles with a particle size in the range of 100 nm to 500 nm and particles with a particle size in the range of 1 nm to 5 nm. Linear protrusions are formed in a mesh-like pattern on the surface, and multiple substantially flat regions with an average diameter in the range of 50 μm to 250 μm are formed, separated by these protrusions. A carbon foil characterized by being composed solely of carbon and unavoidable impurities.

2. A charge conversion foil characterized by being composed of the carbon foil described in Claim 1.

3. It is composed of the carbon foil described in claim 1, and has a thickness of 5 μg / cm². 2 A charge conversion foil characterized by the above.

Citation Information

Patent Citations

  • Process for producing carbon foil, carbon foil, stripper foil for charge conversion making use of the carbon foil, and carbon foil producing apparatus

    WO2007058224A1